Kerusakan, alkohol, kesehatan Kerusakan Lambung Akibat Konsumsi Alkohol: Dampak dan Penanganannya - Madina Ghassan Nebraska; Jausal, Annisa Nuraisa; Wulan, Anggraeni Janar; Rudiyanto, Waluyo (CV. Jasa Sukses Abadi, 2024)
Alcohol consumption has spread across various social strata of society, especially among teenagers. Health issues caused by alcohol are often overlooked. This article delves into the damage to the stomach caused by alcohol consumption. Alcohol can damage the gastric mucosa layer and disrupt the balance of stomach acid, leading to various conditions such as gastritis, gastric ulcers, and even gastric cancer. Additionally, alcohol can affect the movement of food and fluids in the digestive tract, increasing the risk of acid reflux, which can worsen stomach conditions. The mechanisms of stomach damage by alcohol involve the direct toxic effects of alcohol itself and the chronic inflammation it induces. Although this damage is often not immediately felt, its long-term effects can lead to serious complications. Management of alcohol-induced stomach damage involves lifestyle modifications, such as reducing or ceasing alcohol consumption, and medical treatment to alleviate symptoms and accelerate healing. To prevent further damage, it is important to raise awareness of the risks of alcohol to stomach health and promote a healthy lifestyle. Understanding the impact and management of stomach damage caused by alcohol consumption is crucial in preventing more serious complications.